Systematic molecular and cytogenetic screening of 100 patients with marfanoid syndromes and intellectual disability. (18th March 2013) - Callier, P; Aral, B; Hanna, N; Lambert, S; Dindy, H; Ragon, C; Payet, M; Collod‐Beroud, G; Carmignac, V; Delrue, MA; Goizet, C; Philip, N; et al.
Abstract : The association of marfanoid habitus (MH) and intellectual disability (ID) has been reported in the literature, with overlapping presentations and genetic heterogeneity. A hundred patients (71 males and 29 females) with a MH and ID were recruited. Custom‐designed 244K array‐CGH (Agilent®; Agilent Technologies Inc., Santa Clara, CA) and MED12, ZDHHC9, UPF3B, FBN1, TGFBR1 and TGFBR2 sequencing analyses were performed. Eighty patients could be classified as isolated MH and ID: 12 chromosomal imbalances, 1 FBN1 mutation and 1 possibly pathogenic MED12 mutation were found (17%). Twenty patients could be classified as ID with other extra‐skeletal features of the Marfan syndrome (MFS) spectrum: 4 pathogenic FBN1 mutations and 4 chromosomal imbalances were found (2 patients with both FBN1 mutation and chromosomal rearrangement) (29%). These results suggest either that there are more loci with genes yet to be discovered or that MH can also be a relatively non‐specific feature of patients with ID. The search for aortic complications is mandatory even if MH is associated with ID since FBN1 mutations or rearrangements were found in some patients. The excess of males is in favour of the involvement of other X‐linked genes. Although it was impossible to make a diagnosis in 80% of patients, these results will improve genetic counselling in families.